A4_7 Falling Angels & Demons - Shaw, Elliott; Tudor, Vlad; Winkworth, David (Physics Special Topics, 2012)
This paper investigates the chance of survival when jumping out of a high-flying helicopter. First it is found that the related scene described by Dan Brown in ‘Angels & Demons’ is plausible, and then a different case is considered. By considering the balance of forces and drag caused by using a piece of fabric as an improvised parachute, it was found that a landing on a solid material would very likely cause a fatality whatever the case. However a landing in water may be survivable with good form and an extra-extra-extra-extra-large t-shirt.